SORAS : Additive for arsenic removal from underground water - Nurlin, Abu Samah; Yang Farina, Abd Aziz (2021)
A quick and easy way has been developed to remove arsenic specifically from aqueous solution SORAS. We have designed and synthesized with high loading capacity properties capable of ensuring safe drinking water containing less than 10 ppb arsenic. We employ the bulk polymerization approach with allylthiourea (AT) as monomer and arsenic (As) as template,in synthetizing the IIP. During the leaching process, the template was removed by acidification.